2020
DOI: 10.1021/acsami.0c11101
|View full text |Cite
|
Sign up to set email alerts
|

Highly Characteristic Adsorption Based on Single Crystal {001}-TiO2 Surface Molecular Recognition Promotes Enhanced Oxidation

Abstract: Exploring the adsorption and selective removal mechanism of target pollutants on the catalytic interface is an important research topic in the field of environmental sewage treatment. However, the molecular recognition based on the surface of single crystals is still unclear. Single crystal molecularly imprinted TiO2 (001-MI-TiO2) with a highly exposed {001} plane was prepared by a hydrothermal method to characteristically adsorb and degrade phenol. The kinetics of phenol oxidation on 001-MI-TiO2 was 12.93 tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…As a metal-free, environmentally friendly visible light absorbable photocatalyst, polymeric carbon nitride (PCN) has raised wide concern in photodegradation of pollutants, [17][18][19] reduction of CO 2 , 20,21 H 2 production [22][23][24] and, in particular, organic photosynthesis. [25][26][27][28][29][30][31][32][33] Many works had been reported that the surface modified methods can regulate the catalytic performance of the polymeric carbon nitride, and even control the selectivity of the reaction. For instance, our group has previously reported that the cyano modified PCN can selective control the conversion of benzylamine to imine.…”
Section: Introductionmentioning
confidence: 99%
“…As a metal-free, environmentally friendly visible light absorbable photocatalyst, polymeric carbon nitride (PCN) has raised wide concern in photodegradation of pollutants, [17][18][19] reduction of CO 2 , 20,21 H 2 production [22][23][24] and, in particular, organic photosynthesis. [25][26][27][28][29][30][31][32][33] Many works had been reported that the surface modified methods can regulate the catalytic performance of the polymeric carbon nitride, and even control the selectivity of the reaction. For instance, our group has previously reported that the cyano modified PCN can selective control the conversion of benzylamine to imine.…”
Section: Introductionmentioning
confidence: 99%
“…The photodegradation mechanism of organic pollutants in seawater by TiO 2 -based catalysts is discussed here. During the heterogeneous photocatalysis process, the photocatalysts (like TiO 2 ) first adsorb some pollutants to form an interaction with the catalyst surface, before irradiation. , After light excitation, TiO 2 first forms photogenerated holes and electrons. ,, Then, the photogenerated holes directly decompose organic matter on the catalyst surface, or the holes react with adsorbed water and hydroxyl groups to form • OH and degrade organic matter. , These two processes could be considered as surface reactions, as shown in Figures and . In addition, the photogenerated holes and electrons may diffuse into the bulk phase to react with water or oxygen to generate • OH and • O 2– , which further decomposes organic pollutants in the bulk phase of the wastewater.…”
Section: Resultsmentioning
confidence: 99%
“…During the heterogeneous photocatalysis process, the photocatalysts (like TiO 2 ) first adsorb some pollutants to form an interaction with the catalyst surface, before irradiation. 20,21 After light excitation, TiO 2 first forms photogenerated holes and electrons. 12,13,20 Then, the photogenerated holes directly decompose organic matter on the catalyst surface, or the holes react with adsorbed water and hydroxyl groups to form…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to address the above-mentioned problems, scientic researchers have carried out many explorations, including doping with metal and non-metallic ions, codoping, coupling with semiconductors and exposure of specic crystal planes. [25][26][27][28][29][30][31][32][33][34][35][36] The above ways effectively improve the photocatalytic activity of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%